Income Determinants of Women in East Java's Informal Labor Market: Microdata Approach - Wildan Syafitri; Bahtiar Fitanto; Axellina Muara Setyanti; Nurul Izza (Universitas Pendidikan Ganesha, 2023)
Women frequently engage in small businesses related to the informal sector and make a significant contribution to the economy but frequently face gender discrimination and poor working conditions. This study aimed to analyze the determinants of female workers' income in the informal sector using microdata from SAKERNAS 2020. This study found several vital conclusions emerge. Firstly, an increase in the number of years of schooling positively influences the likelihood of attaining a decent income. Secondly, age initially positively affects decent income, but it decreases after reaching a certain age, indicating diminishing returns. Marital status plays a significant role, as married women in the informal sector are less likely to achieve decent income. Additionally, rural residence reduces the likelihood of decent income compared to urban living. Lastly, proficiency in internet usage significantly enhances the likelihood of decent income. The research contributes novel insights into the determinants of female workers' income in the informal sector, shedding light on specific factors that influence income levels, offering a valuable resource for policymakers, researchers, and advocates working towards gender equality and improved economic conditions in this sector.